HealthKick: a nutrition and physical activity intervention for primary schools in low-income settings - Abrahams Zulfa; Dalais Lucinda; Hill Jillian; Fourie Jean; Lambert Estelle V; de Villiers Anniza; Draper Catherine E; Steyn Nelia P (BMC, 2010)
Abstract Background The burden of non-communicable diseases, including type 2 diabetes, is growing in South Africa. This country has a complex mix of over- and under-nutrition, especially in low-income communities, and concerning levels of physical inactivity in children and youth. This paper describes HealthKick, a school-based nutrition and physical activity intervention in primary schools in these settings aimed at reducing diabetes risk factors. Methods/Design This study includes schools within historically disadvantaged, low-income communities from an urban area close to the city of Cape Town and from two rural areas outside of Cape Town, South Africa. The three Educational Districts involved are Metropole North, Cape Winelands and the Overberg. The study has three phases: intervention mapping and formative assessment, intervention development, and outcome and process evaluation. Sixteen schools were purposively selected to participate in the study and randomly allocated as intervention (eight schools) and control (eight schools). The primary aims of HealthKick are to promote healthful eating habits and increase regular participation in health-enhancing physical activity in children, parents and teachers, to prevent overweight, and reduce risk of chronic diseases (particularly type 2 diabetes); as well as to promote the development of an environment within the school and community that facilitates the adoption of healthy lifestyles. The components of HealthKick are: action planning, toolkit (resource guide, a resource box and physical activity resource bin), and an Educators' Manual, which includes a curriculum component. Discussion This study continues to highlight the key role that educators play in implementing a school-based intervention, but that developing capacity within school staff and stakeholders is not a simple or easy task. In spite of the challenges experienced thus far, valuable findings are being produced from this study, especially from Phase 1. Materials developed could be disseminated to other schools in low-income settings both within and outside of South Africa. Owing to the novelty of the HealthKick intervention in low-income South African primary schools, the findings of the evaluation phase have the potential to impact on policy and practice within these settings.